If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -6y = -12 Solving -7x + -6y = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. -7x + -6y + 6y = -12 + 6y Combine like terms: -6y + 6y = 0 -7x + 0 = -12 + 6y -7x = -12 + 6y Divide each side by '-7'. x = 1.714285714 + -0.8571428571y Simplifying x = 1.714285714 + -0.8571428571y
| 0=4x^4-12x^2+6 | | -3x-5y=-13 | | -1/3+6=x-10 | | 2(6x+7)=3(4x+1) | | 5(x^2+4x+4)+34x+68-7=0 | | 4x^3-9=36x-x^2 | | 8(z-3)+11=19 | | 20m^3-25m^2+4m-5= | | f/9=4/6 | | 6-2x-9=1x+11+4x | | 4x-2=-3x+5 | | -x+7y=-15 | | 15x=3(x+5) | | -2z^2+20z-50= | | 2x^3-13x-7=0 | | 5*1+1= | | 200000000/4600000000=x/365 | | 5*2+5*1-3= | | -y^3-6y^2-9y=0 | | x^2+16x+64=13 | | 15/x+4=15/x-5 | | -6-9[4-8b]=-42 | | -9v+29=-4(v-1) | | [n+6]+3=19 | | 0=-12-1x-1x^2 | | 4*3-10= | | 8x^2+8x-17=4-9x | | y=-x^2-x-12 | | 19+5(4-1)= | | 31-2y=-4y+3 | | 6x^2+16x+6=0 | | 0=-6+-1x+x^2 |